CML20, an Arabidopsis Calmodulin-like Protein, Negatively Regulates Guard Cell ABA Signaling and Drought Stress Tolerance - Wu, Xiaomeng; Qiao, Zhu; Liu, Huiping; Acharya, Biswa R.; Li, Chunlong; Zhang, Wei (Frontiers in Plant Science, 2017)
Guard cells shrink in response to drought and abscisic acid (ABA), which is caused by efflux of ions that in turn reduces stomatal aperture and improves the plant’s ability to retain moisture. Cytosolic free calcium is an essential secondary messenger in guard cell ABA signaling, but the details of this regulatory pathway remain sketchy. Here, the calmodulin-like protein CML20, which has four EF-hand domains and calcium-binding activity in vitro, was found to be a negative regulator of ABA-induced stomatal movement in Arabidopsis. The guard cells of cml20 loss-of-function mutant plants were hypersensitive to both ABA-activated S-type anion currents, and ABA inhibited inward K+ currents than those of wild type. Additional, due to smaller stomatal aperture, cml20 showed less water loss from the leaves than wild type. These phenotypes of CML20 overexpressing plants contrasted with wild type in the opposite direction. In the cml20 mutant, the transcripts of stress responsive genes, such as MYB2, RAB18, ERD10, COR47, and RD29A were up-regulated in response to drought and ABA, while down-regulated of APX2 transcription and higher reactive oxygen species (ROS) accumulation. These observations support the CML20, a functional Ca2+ sensor, is a negative regulator in guard cell ABA signaling.